Wittgenstein, a life : young Ludwig, 1889-1921 - McGuinness, Brian (University of California Press, 1988)
Traces the early years of the philosopher, detailing the roles that his troubled family, his imposing and wealthy father, turn-of-the-century Viennese intellectuals, and his World War I experiences played in the formation of his philosophy